Effects of an in-vehicle eco-safe driving system on drivers' glance behaviour. (January 2019) - Li, Xiaomeng; Vaezipour, Atiyeh; Rakotonirainy, Andry; Demmel, Sebastien
Highlights: Effects of eco-safe driving HMI system on drivers' glance behaviours were evaluated. Four information display conditions were tested including BL, AO, FO and AF. Drivers' visual attention on forward roadway was improved in AO and FO conditions. Drivers adapted their visual scanning strategies according to traffic situations. No evidence was established that the HMI system caused driver distraction. Abstract: We have designed a new in-vehicle eco-safe driving system and shown its effectiveness in prompting drivers to execute a fuel-saving and safe driving style (Vaezipour et al., 2018, submitted for publication). However, the system could also bring potential negative outcomes, i.e. driver distraction. This simulator study investigated drivers' glance behaviours as indicators of driver distraction when using our Eco-Safe Human-Machine-Interface (HMI). Four types of eco-safe information display conditions (baseline, advice only, feedback only, both advice and feedback) were tested on different traffic situations with varied road traffic complexity. Results showed that the eco-safe HMI system did not cause visual distraction. In contrast, the advice only or feedback only information improved forward gazing on the roadway. In addition, drivers tended to adapt their visual scanning strategies according to the traffic situations. In the car-following situation they paid longer glances to the forward roadway, while in the intersections they spent more time to look at the HMI system. The findings indicated that our eco-safe driving system improved drivers' eco-safe behaviours and meanwhile enhanced their visual attention on road while no evidence showed that drivers were distracted by it.